2018
DOI: 10.1159/000488378
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial-Stress, Liver Regeneration and Weight Gain: a Conspicuous Pathophysiological Triad

Abstract: Psychosocial stress alters several physiological parameters resulting in multiple disorders, particularly compromising the immune system thereby provoking various diseases including liver disorders. However, the plausible underlying mechanisms remain elusive. Recent literature provides mechanistic evidences of detrimental effects of psychosocial stress on physiology of different body organs including liver. The data of stress-induced pathophysiological changes in liver functions and obesity were systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 54 publications
(84 reference statements)
0
4
0
Order By: Relevance
“…It has been reported that these reactions may disrupt the inflammatory response, 34 increase fat accumulation 35 and inhibit regeneration in the liver. 36 In addition, a cohort study conducted by Russ et al 37 found that mental stress increased the risk of death from liver disease, and a dose-response relationship was observed, suggesting that psychosocial stress caused by long working hours may partially contribute to liver damage. However, current study did not perform a quantitative stress evaluation; hence, it was not possible to analyze the association between stress and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that these reactions may disrupt the inflammatory response, 34 increase fat accumulation 35 and inhibit regeneration in the liver. 36 In addition, a cohort study conducted by Russ et al 37 found that mental stress increased the risk of death from liver disease, and a dose-response relationship was observed, suggesting that psychosocial stress caused by long working hours may partially contribute to liver damage. However, current study did not perform a quantitative stress evaluation; hence, it was not possible to analyze the association between stress and liver damage.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoid-mediated Nrf2 activation also plays an important role in various other physiological and pathological settings. In liver regeneration, Nrf2 has been shown to be a key player (Ishtiaq et al, 2018). A variety of factors regulate hepatic tissue regeneration, among them, augmenter of liver regeneration (ALR) (Dayoub et al, 2013).…”
Section: Modulation Of Nrf2 By Steroidal Anti-inflammatory Drugs (Sads)mentioning
confidence: 99%
“…Some studies have shown that the proportion of patients with liver fibrosis and cirrhosis who experience psychological disorders, such as depression and anxiety, is as high as 50%, which in turn seriously affects the therapeutic effect of liver disease and the quality of life in patients ( Bajaj et al., 2017 ). Over recent years, the effect of chronic psychological stress on exacerbation of hepatitis and progression of liver fibrosis has been acknowledged as a relevant factor ( Ishtiaq et al., 2018 ; Soto-Angona et al., 2020 ). However, its mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%